2022
DOI: 10.5751/ace-02110-170133
|View full text |Cite
|
Sign up to set email alerts
|

Land cover habitat associations of breeding marsh birds and priority waterfowl differ in eastern Canada

Abstract: Waterfowl (ducks, geese, swans) are among the few bird groups showing recent population increases in North America. By contrast, marsh birds (bitterns, rails, grebes) are declining, despite this group appearing to benefit from many of the same conservation actions applied for waterfowl. To help understand this dichotomy, we 1) assessed land cover habitat associations for breeding marsh birds and priority waterfowl in eastern Canada at a broad range of spatial scales, and 2) compared these results between guil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…There is some evidence that waterfowl act as umbrella species for SMBs; Bradshaw et al (2020) reported that on public wetlands in Illinois, USA, SMB occupancy peaked at wetlands with intermediate levels of waterfowl management intensity. Yet other researchers reported waterfowl and SMBs have significantly different habitat associations (Valente et al 2011, Studholme et al 2022. Despite the dearth of information and contradictory outcomes from past researchers, concerns over SMB declines have prompted interest in SMB-focused management at some public wetlands.…”
mentioning
confidence: 99%
“…There is some evidence that waterfowl act as umbrella species for SMBs; Bradshaw et al (2020) reported that on public wetlands in Illinois, USA, SMB occupancy peaked at wetlands with intermediate levels of waterfowl management intensity. Yet other researchers reported waterfowl and SMBs have significantly different habitat associations (Valente et al 2011, Studholme et al 2022. Despite the dearth of information and contradictory outcomes from past researchers, concerns over SMB declines have prompted interest in SMB-focused management at some public wetlands.…”
mentioning
confidence: 99%